2020
DOI: 10.1590/1984-0462/2020/38/2018112
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Physical Activity and Sedentary Behavior Indicators in South-American Preschool Children

Abstract: Objective: To summarize indicators and describe in detail the methods used to physical activity and sedentary behavior measurement in South American preschool children. Data source: In 2017, we searched for articles on researches carried out in South American countries, which presented physical activity and/or sedentary behavior indicators in children aged two to six years. These searches were conducted in Spanish, English, and Portuguese in four electronic databases (LILACS, PubMed, SciELO, and Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
14
0
5
Order By: Relevance
“…The majority of children from our study had a healthy BMI z-score and high levels of PA. The average amount Guerra et al (2020) in a systematic review with South-American preschoolers. Nonetheless, only 3% of the entire sample complied with the combined PA, screen time and sleep time recommendations, which is considerably lower than the prevalence observed in children from high-income countries (10%-15%; Chaput et al, 2017;Cliff et al, 2017;De Craemer et al, 2018), and in children from a pilot study conducted in urban and rural areas from South Africa (26%) (Catherine et al, 2020), a middleincome country as Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of children from our study had a healthy BMI z-score and high levels of PA. The average amount Guerra et al (2020) in a systematic review with South-American preschoolers. Nonetheless, only 3% of the entire sample complied with the combined PA, screen time and sleep time recommendations, which is considerably lower than the prevalence observed in children from high-income countries (10%-15%; Chaput et al, 2017;Cliff et al, 2017;De Craemer et al, 2018), and in children from a pilot study conducted in urban and rural areas from South Africa (26%) (Catherine et al, 2020), a middleincome country as Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…De Craemer et al (2018) showed lower compliance values for Belgian preschool‐aged children, according to week and weekend days (10.1% and 4.3%, respectively), with the lowest compliance seen for the PA recommendations. Conversely, a recent systematic review with South‐American preschoolers reported that a great number of studies has presented moderate PA levels exceeding 60 minutes per day, and a high exposure to screen time, though almost half of the studies used subjective measures of PA, and the adherence to the combined recommendations have not been assessed (Guerra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…É imprescindível que estratégias de comunicação e de disseminação sobre as recomendações, bem como ações apropriadas de promoção da atividade física sejam empregadas para gerar um impacto positivo nos indicadores de atividade física do país 20 . Considerando que dados sobre o nível de atividade física em crianças brasileiras em idade pré--escolar são escassos 30 , essas recomendações poderão dar suporte ao monitoramento e avaliação dos níveis de atividade física de crianças até cinco anos, e consequentemente, dar direcionamentos as pesquisas na área 14 . Além disso, as recomendações brasileiras de atividade física para crianças até 5 anos podem servir de base para o estabelecimento de metas e objetivos para políticas nacionais que visem aumentar a atividade física de crianças em idade pré-escolar 15 .…”
Section: Discussionunclassified
“…The World Health Organization recommends that preschool-aged children spend a minimum of 3 hours a day in a variety of physical activities, with 60 minutes of moderate to vigorous physical activity (MVPA); accumulate less than 60 minutes of sedentary screen time; and sleep between 10 to 13 hours every day [11]. However, little is known about the proportion of South American children meeting these recommendations, including children from Brazil [12]. Currently there is substantial inconsistency in how movement behaviors are measured, and validated assessment tools culturally adapted to LMIC families are lacking.…”
Section: Introductionmentioning
confidence: 99%